Internet technology handbook : - Miller, Mark A. (Wiley Interscience, 2004)
A comprehensive reference that addresses the need for solid understanding of the operation of IP networks, plus optimization and management techniques to keep those networks running at peak performance * Uniquely distinguished from other books on IP networks, as it focuses on operation and management support, and is not just another treatise on protocol theory * Includes many practical case studies as further illustration of the concepts discussed.